ХРОМАТО-МАС-СПЕКТРОМЕТРИЧНЕ ДОСЛІДЖЕННЯ ЕФІРНОЇ ОЛІЇ БРУНЬОК ТОПОЛІ ІТАЛІЙСЬКОЇ - Рудник, А. М. (Фармацевтичний часопис, 2015)
GC/MS RESERCH OF ESSENTIAL OIL OF LEAF-BUDS OF POPULUS NIGRA VAR. ITALICA DU ROI A. M. Rudnik National University of Pharmacy, Kharkiv Department of pharmacognosy Summary: by the method of GC/MS 34 volatile compounds from leaf-buds of Populus nigra var. italica Du Roi, cultivated in Ukraine, were identified. Major of them were sesquiterpen alcochols – bulnesol (31.32%), gvajol (26.49%) and evdesmol isomers (26.49%). The essential oil content was 10644 mg/kg. Keywords: Populus nigra var. italica Du Roi, leaf-buds, essential oil, GC/MS. Introduction. Black poplar (Populus nigra L.) from the family of willow (Salicaceae) belongs to the european-asian group of black poplars section. Wide distribution area of this species, different climatic conditions of growth, the ancient history of cultivation has led to the fact that today scientists have described numerous forms, clones, races and varieties of black poplar, which are often mistakenly identified as a separate species [1, 2]. Buds of black poplar in different times were included in the Pharmacopoeia of the USSR and Russia, aa anti-inflammatory, antipyretic and antibacterial agents. There is evidence that the chemical composition of black poplar buds similar with propolis [3]. Poplar buds for the first time, as a herbal drugs, registered in 1974, but they are not included to Pharmacopoeia of Ukraine. The goal of this work was the study of the component composition of volatile compounds leaf-buds of cultivated in Ukraine decorative form of black poplar – Italian poplar (Populus nigra var. italica Du Roi), to identify opportunities of using them together with the buds of other species of poplars. Research methods. The buds was harvested in april 2013 from the trees growing in the botanical garden of V. N. Karazin Kharkiv national University. For analysis was used only leaf-buds. Composition of volatile compounds of buds was examined using the Agilent Technologies 6890N chromatograph with mass spectrometric detector 5973N [4]. At the National Institute of vine and wine "Magarach" of Ukrainian Academy of agrarian Sciences. Results and discussion. In ieaf-buds of Italian poplar found 46 volatile compounds, of which 34 identified. The essential oil content amounted 10644 mg/kg. Among the identified compounds a large portion of oxygen-containing 20 compounds, which are represented mainly by terpinolene, the remaining 14 compounds, not containing oxygen, is represented by terpenes and saturated hydrocarbons (tri-, tetra-, penta-, gepta-, nonacosane). The total content of the latter is 10,43%. Terpene compounds of essential oil of Italian poplar leaf-buds is represented mainly sesquieres, among which by far dominate bicyclic sesquiterpenoids: bulnesol (31.32%), gvajol (26.49%) and evdesmol isomers (26.49%). It should be noted that according to the data given in [5] the dominant component of the essential oil of the kidneys black poplar, growing on the territory of Croatia is eudesmol (19,6%). Conclusions. For the first time by the method of GC/MS to determine the composition and content of volatile compounds leaf-buds of Italian poplar (Populus nigra var. italica Du Roi.), which is widely cultivated in Ukraine. 2. The essential oil content in the buds amounted 10644 mg/kg. The dominant components are sesquiterpene alcohols bulnesol, gvajol and eudesmol isomers. 3. It is established that the chemical composition of the essential oil of leaf-buds of Populus nigra var. italica Du Roi. significantly different from the essential oil of leaf-buds of Populus nigra L. References 1. Consensus document on the biology of Populus L. Directorate for environmental protection Organisation for Economic cooperation and Development. – Paris, 2000. – 25 p. 2. Rudnik A. M. The Balsam poplars is a promising medicinal plants (literature review) // A. M. Rudnik, V. M. Kovalev, N. V. Borodina // Phytotherapy Journal. – 2008. – № 3. – P. 58-61. 3. Braslavsky V. B. The study of electronic spectra of flavonoids of propolis and poplar / V. B. Braslavsky, V. A. Kurkin // Medical almanac. – 2011. – № 2. – P. 140-144. 4. Chernohorod L. B. Essential oils of some species of the genus Achillea L., containing fragranol / L. B. Chernogorod, B. A. Vinogradov // Plant resources. – St. Petersburg. – 2006. – Vol. 42. – № 2. – P. 61-68. 5. Jerkovic I. Volatile compounds from leaf-bubs of Populus nigra L. (Salicaceae) / I. Jerkovic, J. Mastelic // Phytochemistry. – 2003. – № 63. – P. 109-113.